Stratigraphic signature of the Perito Moreno ice-dammings during the Little Ice Age (southern Patagonia, Argentina). (March 2022) - Caffau, Mauro; Lodolo, Emanuele; Donda, Federica; Zecchin, Massimo; Lozano, Jorge G; Nasi, Federica; Bran, Donaldo M.; Tassone, Alejandro; Caburlotto, Andrea
The spectacular water outburst occurring semi-periodically when the ice-dam formed by the external front of the Perito Moreno glacier collapses, is one of the most attracting events in the UNESCO 'Parque Nacional Los Glaciares' of southern Patagonia. These occurrences have been documented since 1936. Instead, evidence of previous events has been only indirectly provided by dendrochronology analysis. Here we show for the first time radiocarbon-dated sediment cores collected within a small inlet of Brazo Sur, that is, the southern arm of Lago Argentino that record ice-dammings in the Little Ice Age, at 324–266 cal yrs BP, as measured on a vegetal fragment sampled at ca. 14 cm from the top of a core. A common characteristic of the three sediment cores is the abrupt change in the stratigraphic record found at variable depths of 14–18 cm from the top of the cores. This change is marked by a hiatus spanning ca. 3200 years, separating planar-laminated sediments below from an alternation of erosional and depositional events above it, indicating recurring high-energy conditions generated by the emptying of the lake basin. In addition, we observed significant changes in the abundance of environmental indicators as testate amoebae below and above the hiatus. These well-preserved stratigraphic records highlight the key role of glaciolacustine deposits in reconstructing the glacial dynamics and palaeoclimate evolution of a glaciated region.